Application of Buerger Allen Exercise in Patients with Diabetes Mellitus with Ineffective Peripheral Perfusion Nursing Problems : Case Study Report - Febriani, Vrima Ayu; Rohma, Naylil Mawadda (Universitas Tribhuwana Tunggadewi, 2025)
Diabetes mellitus is a disease characterized by uncontrolled hyperglycemia, which disrupts peripheral blood flow due to the accumulation of sugar products in the blood, disrupting nerve impulse transmission and damaging blood vessel walls. One way to improve blood circulation in the legs is through the Buerger Allen Exercise, using the ankle-brachial index as an assessment indicator. This study employed a problem-solving method with a nursing care approach. The author employed a descriptive technique, highlighting the patient's facts and circumstances. After the Buerger Allen Exercise nursing intervention, Mrs Y's ABI increased from 0.79 (moderate) on day 1 to 1.0 (normal) on day 5. After nursing intervention with Buerger Allen Exercise, the ABI value increased. With the increase in the ABI value, peripheral perfusion also increased followed by the achievement of the desired outcome criteria. So the problem of ineffective peripheral perfusion nursing in Mrs Y was resolved. It can be concluded that Buerger Allen Exercise can increase ABI values in patients with type 2 diabetes mellitus with ineffective peripheral perfusion nursing problems.